2013
DOI: 10.1063/1.4826904
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of the influence of different environments on degradation processes in F8BT: Correlating optoelectronic properties with Raman measurements

Abstract: There is a growing interest in conjugated polymers from both industrial and academic points of views. The reasons are their tunable optoelectronic properties, ease of production, and excellent mechanical properties. However, the ease with which their optoelectronic properties are tunable make devices based on them prone to fast degradation and therefore, short life time. The issue of degradation of organic based optoelectronic devices is the topic of many ongoing researches. However, much less attention is giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Poly(fluorene) polymers degrade in the presence of oxygen to form keto (9-fluorenone) defect sites, with a possible carboxyl defect as an intermediate. 66,67 Photodegradation of CPs is also known to occur in the absence of oxygen, including for F8BT, 68,69 other poly-(fluorenes), 70 PH3T, 71 other thiophenes, 72 and PPV-type polymers. 73 In general, the degradation has been attributed to cross-linking and other reactions involving radicals (e.g., chain scissions, Norrish, photo-Fries).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(fluorene) polymers degrade in the presence of oxygen to form keto (9-fluorenone) defect sites, with a possible carboxyl defect as an intermediate. 66,67 Photodegradation of CPs is also known to occur in the absence of oxygen, including for F8BT, 68,69 other poly-(fluorenes), 70 PH3T, 71 other thiophenes, 72 and PPV-type polymers. 73 In general, the degradation has been attributed to cross-linking and other reactions involving radicals (e.g., chain scissions, Norrish, photo-Fries).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Indeed, other studies have suggested that poly(fluorenes), and particularly F8BT, have better resistance to photooxidation than many other types of CPs. 68,84,85 In practice, the PB of Pdots will need to be addressed by multiple strategies. When compatible with optical requirements, judicious selection of the CP will be important.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This rapid degradation is mostly due to the lower resistance of these organic polymers to environmental conditions such as air and moisture . Much work has been done in order to optimize optoelectronic devices by understanding degradation mechanisms and their role determining device stability and lifetime. Two main mechanisms of degradation in polyfluorenes are reported in the literature. The first is the formation of fluorenone defect sites (known as keto defects) that act as low-energy (green-band) trapping sites for singlet excitons, which quench the fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…The top-down fabrication process is thus completed with the deposition of F8BT to fill into the arrayed microholes. Organic materials are highly susceptible to degradation in the presence of atmospheric moisture and oxygen, resulting in permanent emission quenching . To mitigate this organic material processing is completed within an anaerobic (O 2 < 0.5 ppm) glovebox environment with hydrogen gas (H 2 ) < 5% in nitrogen (N 2 ).…”
mentioning
confidence: 99%